Sunitinib induced hepatotoxicity in L02 cells via ROS-MAPKs signaling pathway - Tang, Ting-Li; Yang, Yan; Guo, Lin; Xia, Shuang; Zhang, Bikui; Yan, Miao (Frontiers in Pharmacology, 2022)
Sunitinib is a multi-targeted tyrosine kinase inhibitor with remarkable anticancer activity, while hepatotoxicity is a potentially fatal adverse effect of its administration. The aim of this study was to elucidate the mechanism of hepatotoxicity induced by Sunitinib and the protective effect of glycyrrhetinic acid (GA). Sunitinib significantly reduced the survival of human normal hepatocytes (L02 cells), induced the increase of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH). Chloroquine (CQ) and Z-VAD-FMK were applied to clarify the cell death patterns induced by Sunitinib. Sunitinib significantly induced L02 cells death by triggering apoptosis and autophagy acted as a self-defense mechanism to promote survival. Sunitinib exposure caused excessive ROS generation which activated mitogen-activated protein kinases (MAPKs) signaling. Mechanistically, SP600125 (JNK inhibitor) and SB203580 (p38 inhibitor) respectively blocked apoptosis and autophagy induced by Sunitinib. And inhibition of ROS by NAC pretreatment ameliorated the effect of Sunitinib on MAPKs phosphorylation. GA alleviated Sunitinib-induced cell damage by inhibiting apoptosis and autophagy. These results suggested ROS/MAPKs signaling pathway was responsible for Sunitinib-induced hepatotoxicity and GA could be a preventive strategy to alleviate liver injury caused by Sunitinib.